2020
DOI: 10.3390/foods9121784
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Protein Digestibility and Fatty Acid Profile of Commercial Plant-Based Milk Alternatives

Abstract: Plant-based milk alternatives (PBMA) are a new popular food trend among consumers in Europe and North America. The forecast shows that PBMA will double their value by 2023. The objective of this study was to analyze the nutritional value of commercial products in terms of their fatty acid profile and protein digestibility from commercial PBMA. Eight commercially available PBMA were selected for fatty acid analysis, performed with gas chromatography of methylated fatty acids (GC-FAME), and, from these, four com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 93 publications
6
29
0
Order By: Relevance
“…A total of 32 studies were selected according to the inclusion and exclusion criteria. The studies were conducted in 13 different countries: Brazil (59.38%; n = 19) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]; India (6.25%; n = 2) [ 49 , 50 ]; Argentina (3.13%; n = 1) [ 51 ]; Belgium (3.13%; n = 1) [ 52 ]; Canada (3.13%; n = 1) [ 23 ]; Denmark (3.13%; n = 1) [ 53 ]; Germany (3.13%; n = 1) [ 54 ]; Ghana (3.13%; n = 1) [ 55 ]; Iran (3.13%; n = 1) [ 56 ]; Ireland (3.13%; n = 1) [ 57 ]; Nigeria (3.13%; n = 1) [ 58 ]; Pakistan (3.13%; n = 1) [ 59 ]; Turkey (3.13%; n = 1) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 studies were selected according to the inclusion and exclusion criteria. The studies were conducted in 13 different countries: Brazil (59.38%; n = 19) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]; India (6.25%; n = 2) [ 49 , 50 ]; Argentina (3.13%; n = 1) [ 51 ]; Belgium (3.13%; n = 1) [ 52 ]; Canada (3.13%; n = 1) [ 23 ]; Denmark (3.13%; n = 1) [ 53 ]; Germany (3.13%; n = 1) [ 54 ]; Ghana (3.13%; n = 1) [ 55 ]; Iran (3.13%; n = 1) [ 56 ]; Ireland (3.13%; n = 1) [ 57 ]; Nigeria (3.13%; n = 1) [ 58 ]; Pakistan (3.13%; n = 1) [ 59 ]; Turkey (3.13%; n = 1) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…These structural forms interact with protein contents of the ingredients, hence, research and testing of functional properties in terms of physico-chemical composition and sensory evaluation continues to be an area of active research for meat alternatives [77]. Excellent and current reviews (up to 2020) provide details of physico-chemical studies of meat alternatives in the market [76,78,79]. An active area of research is the investigation of reconstruction techniques of plant protein sources.…”
Section: Seed Protein Analogs Of Animal Protein Foodsmentioning
confidence: 99%
“…An active area of research is the investigation of reconstruction techniques of plant protein sources. Shia and Xiong [80] summarized studies in physico-chemical interactions and the aggregation of plant proteins into particles and anisotropic fibrils to impart meat-like texture; they concluded that thermoextrusion is the principal re-constructuring technique for meat-like fiber synthesis from plant proteins [79]. Moreover, some workers are investigating digestibility as regulatory interests seeks more transparency including information on protein bio-availability in commercial meat analog products [39,78,81].…”
Section: Seed Protein Analogs Of Animal Protein Foodsmentioning
confidence: 99%
See 2 more Smart Citations